Manifestations of Non-Violence in the Epic of Gilgamesh. a Modernistic in Thro-Historical Reading Sex as a Modal. - Majid Musheer Ghaib., Assistant Professor; ., . (International Journal of Engineering and Technology, 2018)
The literature of writings about non-violence in the Mesopotamian culture is so little or marginal. But, specialists regarded population of Mesopotamia as the first to write laws in the human history. That asserts the idea that the law of justice and freedom is one of their basic concepts and that the Sumerian wordÂ "amark", freedom, is the oldest word which clearly refers to human rights. This reversed the idea that the empire of Iraq was built on bloodshed and torture to maintain its prestige. The majority of their laws are characterized by Reform, compensation, and punishment of the guilty instead of revenge and Retribution. The oldest literary document refers to this fact so clearly. The document, which some critics and Analysts regarded as the oldest treasure of epic literature in the human history. The best products of this literature is Gilgamesh, which used a type of non-violence known as the power of sex, magic, and woman's attractions against strong enemies created by the goddess for special purposes. Investigating its expressions, the language of Gilgamesh is away from Decency, love, and romance. Its quotes are porn. This power is the opposite of a powerful power represented by the Monster Enkidu. The epic tries to give us a clear legendary image to convince us with the events it included and showed the non-violence and tolerance which characterized the population of Mesopotamia who documented them in their legends and stories.Â Â